PENGARUH DEMOGRAFI WAJIB PAJAK TERHADAP KEPATUHAN PAJAK UKM - Jeremia Felix Hartono; Sri Rustiyaningsih (POLITEKNIK LP3I JAKARTA, 2026)
The aim of this study is to prove the effect of SME owner age, SME owner religion, SME gender, SME business sector, and SME owner educational background on SME tax compliance. The sample for this study consisted of 60 SMEs in the city of Madiun. The sampling method used was purposive sampling. Hypothesis testing was conducted using the independent t-test and ANOVA using SPSS version 24. The findings of this study prove that the age of SME owners, the business sector of SMEs, and the educational background of SME owners have a significant effect on tsosioax compliance. Meanwhile, the religion of SME owners and the gender of SME owners do not affect SME tax compliance.